2021
DOI: 10.1177/1076029621989813
|View full text |Cite
|
Sign up to set email alerts
|

Brain-Derived Neurotrophic Factor, a New Predictor of Coronary Artery Calcification

Abstract: Brain-derived neurotrophic factor (BDNF) plays a functional role in vascular endothelium homeostasis and the alleviation of atherosclerosis. Matrix gla protein (MGP) and Nε-(1-carboxymethyl)-l-lysine (CML) are both confirmed to be VC predictors. This study investigated the association between BDNF, MGP, CML and coronary artery calcification (CAC). Plasma BDNF, MGP, and CML levels were measured in 274 patients who underwent computed tomography to determine the CAC score (Agatston score). It was found that patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 31 publications
1
8
0
Order By: Relevance
“…Eight studies reported on an association between MGP and arterial calcification ( Janus et al, 2021 ; Pesaro et al, 2018 ; Wilund et al, 2008 ; Acar et al, 2012 ; Jin et al, 2021 ; Jono et al, 2004 ; O'Donnell et al, 2006 ; Silaghi et al, 2013 ). Five reported a positive association ( Janus et al, 2021 ; Pesaro et al, 2018 ; Jin et al, 2021 ; O'Donnell et al, 2006 ; Silaghi et al, 2013 ), one a negative association ( Jono et al, 2004 ) and two a non-significant association ( Wilund et al, 2008 ; Acar et al, 2012 ). There were no longitudinal studies included.…”
Section: Resultsmentioning
confidence: 99%
“…Eight studies reported on an association between MGP and arterial calcification ( Janus et al, 2021 ; Pesaro et al, 2018 ; Wilund et al, 2008 ; Acar et al, 2012 ; Jin et al, 2021 ; Jono et al, 2004 ; O'Donnell et al, 2006 ; Silaghi et al, 2013 ). Five reported a positive association ( Janus et al, 2021 ; Pesaro et al, 2018 ; Jin et al, 2021 ; O'Donnell et al, 2006 ; Silaghi et al, 2013 ), one a negative association ( Jono et al, 2004 ) and two a non-significant association ( Wilund et al, 2008 ; Acar et al, 2012 ). There were no longitudinal studies included.…”
Section: Resultsmentioning
confidence: 99%
“…Coronary CTA images were reviewed by two experienced radiologists who were blind to all clinical profiles of the participants. CAC score was calculated by dedicated software and quantified as the Agatston score [11]. According to the ACCF/AHA 2007 clinical expert consensus, the Agatston score was divided into 4 levels (0, 1-100, 101-400, > 400) [12].…”
Section: Ct Angiographymentioning
confidence: 99%
“…Coronary CTA images were reviewed by two experienced radiologists who were blind to all clinical pro les of the participants. CAC score was calculated by dedicated software and quanti ed as the Agatston score 9 . According to the ACCF/AHA 2007 clinical expert consensus, the Agatston score was divided into 4 levels (0, 1-100, 101-400, >400) 10 .…”
Section: Ct Angiographymentioning
confidence: 99%